Determinants of Dryland Farmer Household Food Security - Endang Tri Astutiningsih; Bonar M. Sinaga; Nunung Kusnadi; Handewi P. Saliem (Postgraduate, University of Mataram, 2026)
Food security is a central issue that must be realized at the household level. Poverty and food insecurity are the most common problems faced by people living in drylands. This study aims to analyze the food security status of dryland farmer households and the factors that determine it. The unit of analysis in this study is dryland farmer households growing upland and paddy rice in Sukabumi Regency, West Java. Food security is analyzed using descriptive methods, while its determinants are analyzed using a simultaneous equation model estimated by the 2SLS method. The research results show that farmer households are in a state of food insecurity. The energy consumption rate, as an indicator of food security, is significantly influenced by both food and non-food expenditures. Upland rice production positively affects the value of food reserves, and its development can support the realization of household food security in drylands.